A Microporous Hydrogen-Bonded Organic Framework: Exceptional Stability and Highly Selective Adsorption of Gas and Liquid - Luo, Xu-Zhong; Jia, Xin-Jian; Deng, Ji-Hua; Zhong, Jin-Lian; Liu, Hui-Jin; Wang, Ke-Jun; Zhong, Di-Chang (Journal of the American Chemical Society, 2013)
An extremely stable hydrogen-bonded organic framework, HOF-8, was fabricated. HOF-8 is not only thermally stable but also stable in water and common organic solvents. More interestingly, desolvated HOF-8 exhibits high CO2 adsorption as well as highly selective CO2 and C6H6 adsorption at ambient temperature.